A new climate for Europe: 2030 climate targets must be more ambitious - Pao-Yu Oei; Karlo Hainsch; Konstantin Löffler; Christian R. von Hirschhausen; Franziska Holz; Claudia Kemfert (DIW Weekly Report, 2019)
Amidst other national and global climate protection initiatives, the new EU Commission under the leadership of Ursula von der Leyen is facing the challenge of concretely following through on previous announcements regarding an ambitious climate policy. Specifically, action must be taken to raise the 2030 climate targets and the 2050 long-term strategy must be revised in adherence with the Paris Agreement. Model calculations by DIW Berlin economists show that it is possible and economically feasible to increase the 2030 emission reduction target from 40 to 60 percent compared to 1990. The considerable environmental cost savings are offset by small increases in energy system costs. When implementing an aggressive climate policy, burden sharing between the member states must be considered. Furthermore, neither nuclear power nor CO2 capture technology is needed to implement these ambitious climate targets, as the results of European model scenarios from the SET-Nav project show.
Keywords: Q54; Q53; Q48; L94; 330; Europe; energy; climate policy; technologies